Study of Stages and Ethnolinguistics of Tu'a Eja Culture of Keo Ethnic, Nagekeo Tribe, Flores, East Nusa Tenggara, Indonesia in Efforts of Local Cultural Wisdom Preservation - Mansuetus Mola (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Traditional marriage in Keo ethnic language are called tu'a eja. Tu'a eja procession with complete stages is form of respect for women who still maintain their chastity. This implies that tu’a eja teaches values and norms that regulates social interactions of younger generation. This is interesting to review, but data on stages and vocabulary meaning in tu’a eja process have not been found. This study aimed to determine the stages and vocabulary meanings of the process of tu'a eja. Type of this research was qualitative research used interview, observation and documentation used descriptive data analysis techniques. The results showed that there were 8 stages of traditional process of tu'a eja, namely: asking (pai holo wini or tana ale), engagement (peu lako yongo), family gathering (tiwo ine weta ne'e ane ana), delivery of belis (tu ngawu), giving mat and pillow (ti'i te'e pati lani), moving house (nuka sa'o), family separation (wola ine weta ane ana) and returning to visit origin place (lalo la'e). Each stage used traditional language that contained meanings and messages of values, etiquette and morals for Keo ethnic people. Tu'a eja culture needed to be preserved as local cultural wisdom in Nagekeo tribe, Flores, East Nusa Tenggara.